DIGITAL TRANSFORMATION OF AGRICULTURAL INDUSTRIAL COMPLEX IN THE IMPLEMENTATION OF ITS DEVELOPMENT STRATEGY - Svetlana ALEKSEEVA; Galina VOLKOVA; Olga SUKHANOVA; Elena FUDINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In modern conditions, the innovative development of agriculture has reached a high level and ensures a steady growth in agricultural production. In this regard, the identification of new reserves for the growth of agro-industrial production will give a new impetus to the development strategy of the agro-industrial complex, one of which is the digitalization of agriculture as the basis for the stable functioning and growth of its efficiency. The work of the agricultural sector directly affects the employment, quality and standard of living of millions of Russians, as well as the food and national security of the country. One of the goals of the implementation of the agro-industrial complex development strategy is its digital transformation, which correlates with the national policy to accelerate the introduction of digital technologies in the economy and social sphere. Digital technologies will significantly change the quality of technological process control and decision-making at all levels. The real prospects of the domestic agricultural sector in the direction of digital transformation include the transition to a qualitatively new level of use of agro-industrial technologies - "smart agriculture", including precision farming, smart farms and others using elements of artificial intelligence. The purpose of the publication is to define the concept of "Digital transformation of the agro-industrial complex", analyze the indicators and indicators of the program of digitalization in agriculture and determine the possibilities of using information and digital technologies in agriculture. The work used general and special research methods, including analysis and synthesis, generalization of scientific information, logical method and systematization. The result of the work is an analysis of the current state of agricultural development and systematization of indicators of the digitalization program for agriculture and determination of parameters for the use of digital technologies in crop and livestock production. The use of digital technologies in the agroindustrial complex would increase not only the volumes of production and exports, but also the competitiveness of Russian products. Reasonable use of information technologies could almost double the efficiency of the Russian agro-industrial complex.